Unlocking the potential of early contractor involvement in reducing design risks in commercial building refurbishment projects–a Western Australian perspective - Nibbelink, J.; Sutrisna, M.; Zaman, Atiq (Pergamon, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. The commercial refurbishment sector is widely gaining popularity, particularly in industries such as the Western Australian construction industry in order to effectively house commercial businesses and operations. Unfortunately, commercial refurbishments have long been characterised by its added complexity, risk and uncertainty facing the management and delivery of such projects. The uncertainties are largely attributed to the segregated relationship between design and construction processes. Among a multitude of options in procuring refurbishment projects, the early contractor involvement (ECI) emerged as a procurement route that bridges this typical gap between design and construction, promotes a collaborative design process and offers opportunity for risk mitigation and certainty of delivery. Whilst appearing as a worthy candidate to procure refurbishment of commercial buildings, anecdotal evidence have indicted the potential of ECI to reduce design risks through synergising the contractor’s construction expertise into the design process. In light of this, the paper aims to report the findings from a recent research project conducted in Western Australia on this topic through case study approach. The findings revealed the specific points and activities during design of commercial building refurbishment where the contributions of the contractor are optimum in reducing design risks. This is captured in the resultant process map specifically developed for this type of projects under the ECI scheme. The process map is expected to further support project teams at the early design stage of a commercial building refurbishment projects to devise a robust strategy to fully benefit from procuring their project through ECI.